Efectos del contenido funcional de la instrucción sobre el desempeño en igualación a la muestra de segundo orden (2018)
The effect of the functional content of instructions on the acquisition, transfer and description of performance in a second order matching-to-sample task was evaluated. Twenty undergraduate students were assigned to one of four experimental groups: (a) procedural instruction at the start of the task (PStart); (b) procedural instruction in each trial (PTrial); (c) instruction referring to instances in each trial (ITrial); and (d) instruction referring to relation in each trial (RTrial). The proportion of correct attempts was analyzed, and was found to be higher in the ITrial and RTrial groups for the training phase, and for the PStart, PTrial and RTrial groups in the extra-instance and extra-modal transfer test, as well as for the ITrial group in the extra-relational test; the larger number of accurate performance descriptions was observed in the RTrial group. These results show that abstract stimulus control can be presented either by way of transfer of functions throughout instructions, or by differentiation of positive and negative cases of the contingencies, which is enhanced by the concurrent presence of the instruction and the stimulus array.